A Black Spirit Memoir - Emezi, Akwaeke (Nigeria, 2022)
This book reveals the harrowing yet resolute truths of thier own life. Through candid, intimate correspondence with friends, lovers, and family, Emezi traces the unfolding of a self and the unforgettable journey of a creative spririt stepping into power in the human world...
Keywords: Biography & Autobiography; Non-Fiction